2023
DOI: 10.5430/wjel.v13n2p168
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Cultural Representation through Tourism-Related Cultural Words Translation on Hangzhou Tourism Website

Abstract: This study investigates the translation procedures of the translated cultural words on the tourism website and explores whether the cultural representation is author-oriented or reader-oriented. A descriptive qualitative research method was used in this study. Hangzhou tourism website is selected as the case. 160 cultural words were collected and extracted from the website in total. The results indicated that retention, calque, and paraphrase were widely used translation procedures, and cultural representation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…Transliteration, literal translation, and their combination counting 67.25% are employed dominantly, which represents a conscious effort to prevent the influence of Western cultural mores and prioritizes the maintenance of the cultural and linguistic distinctiveness of the source culture. This finding is consistent with a prior investigation conducted by Chen et al (2023a), which identified foreignization as the prevailing approach in translating tourism texts. In the same vein, Chung (2021) argues that foreignization works in the following ways: it enhances visitors' cultural engagement, prevents ethnocentric biases, aligns with the preferences of the target audience, grants a unique cultural identity, and promotes intercultural exchanges.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Transliteration, literal translation, and their combination counting 67.25% are employed dominantly, which represents a conscious effort to prevent the influence of Western cultural mores and prioritizes the maintenance of the cultural and linguistic distinctiveness of the source culture. This finding is consistent with a prior investigation conducted by Chen et al (2023a), which identified foreignization as the prevailing approach in translating tourism texts. In the same vein, Chung (2021) argues that foreignization works in the following ways: it enhances visitors' cultural engagement, prevents ethnocentric biases, aligns with the preferences of the target audience, grants a unique cultural identity, and promotes intercultural exchanges.…”
Section: Resultssupporting
confidence: 92%
“…The destination culture is accordingly represented and narrated. Translating tourism materials as a cross cultural communication poses great challenges related to non-equivalent issues in the target language (Chen et al, 2023a), making it particularly demanding for translators. Cultural references, inherently culture-specific, are known and unique to one cultural community but not to others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different researchers have different definitions of CSIs based on different standards (Chen, 2023). Vermeer proposed the term "cultureme", and "cultureme is a social phenomenon of a culture X that is regarded as relevant by the members of this culture and, when compared with a corresponding social phenomenon in a culture Y, is found to be specific to culture X.…”
Section: Literature Reviewmentioning
confidence: 99%